AAT study pack : economics and statistics 1/ intermediate paper 8 - Association of Accounting Technicians (London : Financial Training Courses, 1990)
This two volume study pack is designed to provide a complete course of study for paper 8 Economics and Statistics, at the intermediate examination of the Association of Accounting Technicians. This volume provides comprehensive coverage of the economics part of the syllabus. Volume 2 covers the statistics syllabus.
Includes index
rpm 10/04/2017
Loans
Keywords: Economics; The Market; National income analysis; Investment and business cycles; Money and banking; Fiscal/monetary policies; Unemployment and inflation; International trade and finance; National income analysis